Quality expectations in the Malaysian wooden furniture industry: the foreign buyers perspective - Ratnasingam, Jegatheswaran; Chong, Yen Yoon; Mohamed, Shukri; Mohamad Kasim, Mohamad Roslan (Asian Network for Scientific Information, 2013)
Although, the ISO quality management system is often perceived to be marketing tool within the manufacturing industry its implications on the design-sensitive wooden furniture industry remain unknown. Therefore, a survey of 500 foreign furniture buyers was conducted at the Malaysian International Furniture Fair (MIFF) to establish the status and perceived benefits of the ISO-certification in the furniture industry. The results revealed that although furniture purchase decisions is made on the basis of ten major attributes, ISO certification emerged as one of the more important attributes. Nevertheless, the influence of the ISO system on the product marketability is limited to specific markets, especially in Japan, Korea and East Asia which are markets most demanding for ISO certification. On the other hand, ISO certification generally improves the overall performance of the furniture companies and foreign furniture buyers prefer to purchase their merchandise from such companies due to their higher degree of confidence and product consistency. Despite the benefits to be derived, the lack of awareness prevalent among the Small and Medium Enterprises (SMEs) in the furniture sector explains the low adoption level of the system in the furniture sector. Therefore, market demand alone is not sufficient to boost the adoption of the ISO quality system among furniture suppliers. It appears a concerted effort must be drawn up to boost the awareness of benefits to be gained, if ISO certification is to be expanded throughout the industry in the future.